2011
DOI: 10.1007/s00774-011-0307-3
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of subregional vertebral bone mineral density in vitro using lateral projection dual-energy X-ray absorptiometry: validation with peripheral quantitative computed tomography

Abstract: Although a strong relationship exists between areal bone mineral density (aBMD) derived from dual energy X-ray absorptiometry (DXA) and bone strength, the predictive validity of aBMD for osteoporotic vertebral fractures remains suboptimal. The diagnostic sensitivity of DXA may be improved by assessing aBMD within vertebral subregions, rather than relying on an estimate derived from the total area of the vertebra. The objective of this study was to validate a method of measuring subregional vertebral aBMD in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
14
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 51 publications
3
14
0
Order By: Relevance
“…Primarily, this study has shown that DXA can identify differences in srBMD within a vertebra, as displayed by the significant main effect for subregion ( P < 0.05), consistent with earlier data [38, 42, 43]. Secondly, it was found that the GIO group demonstrated significantly lower results for the anterior subregion : whole vertebra ratio (ROI 4 : ROI 1) and the anterior subregion : posterior subregion ratio (ROI 4 : ROI 2) when compared to both the primary osteoporosis and control groups.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Primarily, this study has shown that DXA can identify differences in srBMD within a vertebra, as displayed by the significant main effect for subregion ( P < 0.05), consistent with earlier data [38, 42, 43]. Secondly, it was found that the GIO group demonstrated significantly lower results for the anterior subregion : whole vertebra ratio (ROI 4 : ROI 1) and the anterior subregion : posterior subregion ratio (ROI 4 : ROI 2) when compared to both the primary osteoporosis and control groups.…”
Section: Discussionsupporting
confidence: 92%
“…Subsequent studies have further validated the subregional methodology, establishing high short-term in vivo precision [41], moderate to high intrarater and interrater precision [41], and concurrent validity when compared with pQCT and micro-CT [42]. Validation findings were later replicated using a much larger sample size [43], demonstrating that lateral DXA is valid when measuring heterogeneity in aBMD between intravertebral subregions. Lateral DXA measurement of aBMD has also been shown to be a better predictor of vertebral failure load at both the whole vertebral body [44] and within subregions [45], compared with standard PA DXA.…”
Section: Introductionmentioning
confidence: 99%
“…Another consequence of removing the posterior elements was that simulating anterior–posterior DXA measurements would be much less physiologic than simulating the less commonly used lateral DXA measurements. However, recent studies have shown that aBMD measured by lateral DXA is more strongly correlated with vertebral strength than PA DXA [8, 39], which suggests that the regression models with IQR BMD would also outperform a model using aBMD measured by PA DXA. Third, the applied loading was stepwise, and it is possible that the failure mechanisms differed as compared to the case of application of a steadily increasing load until failure.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence from literature suggests that the heterogeneity of volumetric BMD within a vertebra, in addition to the average volumetric BMD, may be an important determinant of the mechanical properties of a vertebra (Cody et al, 1991; McCubbrey et al, 1995; Yerramshetty et al, 2009) and risk of a clinical vertebral fracture (Dougherty, 1996; Briggs et al, 2012). Much of the experimental evidence comes from tests, in which vertebrae are monotonically loaded and relates BMD heterogeneity to the quasi-static properties of a vertebra (Cody et al, 1991; Yerramshetty et al, 2009).…”
Section: Introductionmentioning
confidence: 99%